Management of sudden sensorineural hearing loss: a prospective study of 30 patients - Khot, Sunil N.; G., Priyadarshini; Kunnumal, Ayisha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Sudden sensorineural hearing loss (SNHL) is sensorineural hearing loss of 30 dB or more over at least three contiguous audiometric frequencies that develop over a period of few hours to three days. The purpose of study is to make a protocol for treatment. Methods: 30 cases of sudden SNHL who presented to OPD of Government Medical College, Miraj between December 2015 to April 2017 were included. Detailed history taking and ENT examination was done. All patients were admitted and started on intravenous methylprednisolone. If hearing improvement was not observed, intratympanic methylprednisolone (ITS) was administered. Results: 50% patients had recovery with intravenous Methylprednisolone and 50% had no recovery. “No recovery” patients were subjected to ITS, of which 20% had complete, 30% partial and 50% no recovery. Among no recovery patients of ITS, 10% had hearing loss greater than 90 dB with improvement rate of 0%; 40% had hearing loss of 90 - 50 dB with improvement rate of 50%; 50% had hearing loss of 50-30 dB with improvement rate of 60%. Among 15 cases of ITS, mean number of days between onset of symptom and starting ITS was 13 days for complete recovery patients; 17.3 days for partial or slight recovery; 20.6 days for no recovery. Conclusions: Hearing loss less than 90 dB and earlier ITS has positive influence on hearing recovery. Systemic steroids are currently the mainstay of initial treatment. ITS is an effective treatment modality for patients who fail to respond to systemic steroids.